2016
DOI: 10.21273/hortsci10996-16
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Commercial Strawberry Cultivars and Advanced Selections as Affected by Season, Harvest, and Postharvest Storage

Abstract: Strawberries are one of the most important food crops grown in Florida, with a harvested area of ≈10,000 acres. The University of Florida strawberry breeding program develops cultivars adapted to this region and its particular weather conditions, with a major aim of increasing overall quality. The objective of this study was to compare the fruit of advanced breeding selections to those of commercial cultivars, for compositional attributes. Seven different strawberry genotypes were compared at harvest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
(68 reference statements)
1
14
0
Order By: Relevance
“…Lower temperatures result in lower metabolic rate and higher accumulation of soluble carbohydrates and starch (Wang and Camp, 2000). Loss of sugars in strawberries postharvest has been reported elsewhere (Kelly et al, 2016b;Kelly et al, 2018) and the degradation occurs regardless of harvest or genotype effects (Cayo et al, 2016). Caleb et al (2016) also observed a depletion of sucrose and glucose in strawberries during storage; highlighting that the role of sucrose, postharvest, is to sustain the energy demand during respiration and support fruit maintenance and metabolic processes.…”
Section: Total Sugar Contentmentioning
confidence: 60%
See 4 more Smart Citations
“…Lower temperatures result in lower metabolic rate and higher accumulation of soluble carbohydrates and starch (Wang and Camp, 2000). Loss of sugars in strawberries postharvest has been reported elsewhere (Kelly et al, 2016b;Kelly et al, 2018) and the degradation occurs regardless of harvest or genotype effects (Cayo et al, 2016). Caleb et al (2016) also observed a depletion of sucrose and glucose in strawberries during storage; highlighting that the role of sucrose, postharvest, is to sustain the energy demand during respiration and support fruit maintenance and metabolic processes.…”
Section: Total Sugar Contentmentioning
confidence: 60%
“…Strawberries harvested in 2012 had significantly higher ANC (4.04 g kg -1 ) compared to strawberries harvested in 2013 (1.69 g kg -1 ), possibly due to the higher temperatures in 2012 on the week before harvest. Differences in ANC between years were reported by Cayo et al (2016), also observing that higher temperatures around time of harvest led to higher accumulation of anthocyanins. Total anthocyanins content decreased with time with significant differences among the different RH conditions.…”
Section: Total Anthocyanin Contentmentioning
confidence: 84%
See 3 more Smart Citations